Effectiveness of Prehospital Epinephrine Administration in Improving Long-term Outcomes of Witnessed Out-of-hospital Cardiac Arrest Patients with Initial Non-shockable Rhythms. (4th July 2017) - Tomio, Jun; Nakahara, Shinji; Takahashi, Hideto; Ichikawa, Masao; Nishida, Masamichi; Morimura, Naoto; Sakamoto, Tetsuya
Abstract: Objective : We evaluated the association between prehospital epinephrine administration by emergency medical services (EMS) and the long-term outcomes of out-of-hospital cardiac arrest (OHCA) with initial pulseless electrical activity (PEA) or asystole.Methods : We conducted a controlled, propensity-matched, retrospective cohort study by using Japan's nationwide OHCA registry database. We studied 110, 239 bystander-witnessed OHCA patients aged 15–94 years with initial non-shockable rhythms registered between January 2008 and December 2012. We created 1–1 matched pairs of patients with or without epinephrine by using sequential risk set matching based on time-dependent propensity scores to balance the patients' severity and characteristics. We compared overall and neurologically intact survival 1 month after OHCA between cases and controls using conditional logistic regression models by category of the initial rhythm.Results : Propensity matching created 7, 431 pairs in patients with PEA and 8, 906 pairs in those with asystole. Epinephrine administration was associated with higher overall survival (4.49% vs. 2.96%; odds ratio [OR], 1.55; 95% confidence interval [CI], 1.30–1.85) but not with neurologically intact survival (0.98% vs. 0.78%; OR, 1.26; 95% CI, 0.89–1.78) in patients with PEA, and with higher overall survival (2.38% vs. 1.04%; OR, 2.34; 95% CI, 1.82–3.00) and neurologically intact survival (0.48% vs. 0.22%; OR, 2.28; 95% CI, 1.31–3.96) in those with asystole.Conclusions : Prehospital epinephrine administration by EMS is favorably associated with long-term neurological outcomes in patients with initial asystole and with long-term survival outcomes in those with PEA.